An Ambitious Primary School Curriculum. - Glazzard, Jonathan; Stones, Samuel (St Albans : Critical Publishing, 2021)
Comprehensive guidance to support those involved in primary education in developing the curriculum to meet the requirements of the new Ofsted (2019) framework.
Building cultural capital through religious education -- Building cultural capital through the co-curriculum -- Evidence-based practice -- Critical questions -- Case study -- Critical questions -- Summary -- Further reading -- Chapter 4 An enquiry-based curriculum -- Introduction -- A rationale for an enquiry-based curriculum -- Enquiry in English -- Mathematical enquiry -- Scientific enquiry -- Case study -- Historical enquiry -- Critical questions -- Ways of investigating a source -- Critical questions -- Geographical enquiry -- Critical questions -- Enquiry in religious education
Description based upon print version of record.
Critical questions.
eBooks on EBSCOhost
Keywords: Education, Elementary -- Curricula -- England; Teacher participation in curriculum planning; Enseignement primaire -- Programmes d'études -- Angleterre; Enseignants -- Participation à la planification des programmes d'études.; Educational Policy & Reform; Teaching Methods & Materials; EDUCATION; Education, Elementary -- Curricula; Teacher participation in curriculum planning; England